Sintesis dan Karakterisasi Nanomagnetik Fe3O4 Berbasis Pasir Besi Pantai Sunur melalui Metode Kopresipitasi - Feby Eriza Tanjung; Rahmat Hidayat; Ratnawulan Ratnawulan; Leni Aziyus Fitri (Lembaga Pengembangan Kinerja Dosen, 2026)
Iron sand is an abundant natural resource in coastal areas of Indonesia, including Sunur Beach, Padang Pariaman Regency, West Sumatra, which has great potential as an economical and environmentally friendly raw material for Fe₃O₄ nanoparticle synthesis. This study aims to synthesize and characterize Fe₃O₄ nanoparticles derived from Sunur Beach iron sand using the coprecipitation method. The synthesis process involved dissolving iron sand in 37% HCl, followed by precipitation using 25% NH₄OH, drying, and sintering at 400°C. The synthesized product was characterized using XRD, FTIR, and FESEM analyses. The XRD results showed a characteristic magnetite phase diffraction pattern with the main peak appearing at the (311) plane according to the ICDD standard 01-075-0449, with an average crystal size of 18.36 nm calculated using the Debye-Scherrer equation. FTIR analysis confirmed the presence of Fe₃O₄ functional groups at wavenumbers of 545.18, 490.81, and 432.32 cm⁻¹, representing the characteristic bonds of magnetite structures. FESEM observations revealed a rod-like particle morphology with an average diameter of 96.48 nm. These results confirm that Sunur Beach iron sand is a viable alternative raw material for nanoscale Fe₃O₄ nanoparticle synthesis.